Evolución de las condiciones de vida en la ciudad de Medellín basados en la encuesta de calidad de vida 2007 (2008)
ABSTRACT: In 2001, the Department of Metropolitan Planning of the city of Medellín realized the Survey of Quality of Vida (ECV), which collected data on the conditions of life of the inhabitants of the city. These indicators allowed obtaining measurements on the conditions of life for the homes in each commune of the urban area, and the five “corregimientos” of the rural area. From the 2001´s, it has been continued realizing the ECV annually with the purpose of to investigate the evolution of the conditions of life of the homes of the city with respect to the found ones in the basic information of year 2001. The objective of this document is to present the update of the measurements of conditions of life in Medellín based on the Survey of Quality of Life for year 2007 and for presenting its evolution from the 2001.